Prescribed burning impacts avian diversity and disadvantages woodland-specialist birds unless long-unburnt habitat is retained. (November 2017) - Prowse, Thomas A.A.; Collard, Stuart J.; Blackwood, Alice; O'Connor, Patrick J.; Delean, Steven; Barnes, Megan; Cassey, Phillip; Possingham, Hugh P.
Abstract: Prescribed burning is a commonly adopted fire-management strategy that attempts to protect human life and assets by removing accumulated, flammable biomass. Heterogeneous burning patterns are often favoured in an attempt to balance fuel-reduction and biodiversity goals under the 'pyrodiversity begets biodiversity' paradigm. Using comprehensive spatiotemporal monitoring data, we quantified the impacts of fire on bird assemblages in the peri-urban temperate woodlands of the Mount Lofty Ranges, South Australia, where the frequency of prescribed burning is increasing. After accounting for regional trends and site effects, sites burnt 20 years previously accommodated 15% fewer birds than unburnt sites, while sites burnt in the preceding year had 22% fewer birds. Fire also modified bird assemblages, favouring generalists and ground-feeding species. Of 60 species considered, 37% were both declining and negatively impacted by recent burning, while burning reinforced increasing trends in 30% of species, particularly large, common birds (e.g., magpies, ravens, wattlebirds). Simulations of avian alpha-, beta- and gamma-diversity under different fire-management scenarios predicted higher avian diversity for scenarios that retained unburnt woodlands relative to those that managed all sites. Relative to a no-fire scenario, for example, burning sites once every 10 years was simulated to reduce the abundance of woodland generalists by 7% and woodland specialists by 10%, while retaining some long-unburnt woodland ameliorated these effects. There is a trade-off between fuel-reduction burning and conservation goals; to maximise avian diversity and avert the replacement of woodland bird species with generalists, fire-management planning should preserve long-unburnt woodland habitat.